MEMBANGUN APLIKASI ORANG TUA ASUH BERBASIS ANDROID PADA SMK RAKYAT PANCUR BATU - Gladis Lavenia Sembiring; Bersama Sinuraya; Jenni Veronika Br Ginting (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
Application comes from the word application, which is the form of a tapply verb whichin Indonesian means processor. In terms of, computer applications are a sub class ofcomputer software that uses capabilities. Another definition of the application is aprogram that is ready to be used that is made to carry out a function for users ofapplication services and the use of other applications that can be used by a target.According to the executive computer dictionary, the application has the meaning of solvingproblems using one of the application data processing techniques that usually races on adesired or expected computation or processing expected data. In addition, the applicationalso has a function as a service for the needs of several activities carried out by humanssuch as systems for buying and selling software, games or online games. The purpose ofthe development of this foster parent application is to bring together donors called fosterparents with students who are foster children, to provide assistance in the form of funds forschool needs, housing, and daily living expenses, this application will also prioritize thestudents receiving assistance are orphans, orphans or orphans. This application is alsounder the supervision of the school, so the school is inputting the data of students whoneed assistance and the costs of the needs of these students.